Actions of academic libraries in the prevention of plagiarism - Leitão, Helena (2019)
The conceptual issue of plagiarism is complex and subjective, thus it is important to understand the practices that constitute an infraction of the good use of information. We propose to highlight and assess the contribution of academic libraries to the prevention of plagiarism following a qualitative methodological approach and a systematic literature review. The aim of our study is to raise awareness about the prevention of plagiarism in the academic community and for this purpose we developed a set of pedagogical recommendations.